Assessment of the first presentations of common variable immunodeficiency in a large cohort of patients - Hossein Esmaeilzadeh; Armita Jokar-Derisi; Amir Hossein Hassani; Reza Yazdani; Samaneh Delavari; Hassan Abolhassani; Negar Mortazavi; Aida Askarisarvestani (BMC Immunology, 2023)
Abstract Background Common Variable Immunodeficiency (CVID) is a primary immunodeficiency syndrome resulting in recurrent infections, autoimmunity, and granulomatous manifestations. Methods and materials This retrospective study was conducted on an Iranian national registry of immunodeficient patients from 2010 to 2021. The frequency of first presentations of CVID and its association with sex, age of onset, and family history of CVID was evaluated. Results A total of 383 patients entered the study, 164 of whom were female, and the rest were male. The mean age of the patients was 25.3 ± 14.5 years. The most frequent first presentations of CVID were pneumonia (36.8%) and diarrhea (19.1%). Patient sex, age of onset, and family history did not make significant differences in first presentations of this disease. Conclusion pneumonia is the most common first presentation of CVID. Family history of CVID, the age of symptom onset, and sex made no differences in the first presentations of CVID.